Reproductive parameters of dairy goats after receiving two doses of d-cloprostenol at different intervals - Maia, A. L. R. S.; Brandao, F. Z.; Souza-Fabjan, J. M. G.; Balaro, M. F. A.; Oliveira, M. E. F. [UNESP]; Faco, O.; Fonseca, J. F. (Elsevier B.V., 2017)
This study evaluated the efficiency of two d-cloprostenol injections at different intervals on the reproductive parameters of dairy goats. Trial 1 comprised 54 goats allocated to receive two 37.5 mu g d-cloprostenol doses at intervals of seven (T-7, n = 19), 10 (T-10, n = 18), and 11.5 (T-11.5, n = 17) days. Trial 2 comprised 62 goats allocated to receive injections at T-7 (n = 30) and T-11.(5) (n = 32). Ultrasonography was done and blood was collected just before d-cloprostenol injections. After the second dose, goats were artificially inseminated (AI) with frozen-thawed semen at 18-24 h (Trial 1) or at 10-24 h (adjusted according to the time of estrus onset in Trial 2) after estrus detection. Estrus response rate did not differ (P > 0.05) among groups in Trials 1 (T-7 = 94.7%; T-10 = 88.9%; T-11.5 = 88.2%) and 2 (T-7 = 90.0%; T-11.5 = 96.9). All females showed progesterone concentrations > 1 ng/mL before both d-cloprostenol injections. The largest follicle diameter present on ovaries was similar (P > 0.05) among treatments at the first and second dose. The second largest follicle diameter was superior (P < 0.05) to T-7 than to T-10 and T-11.5 goats at first dose only. This possibly resulted in lower interval to estrus (P < 0.05) in T-7-treated goats than other treated goats in both trials. The conception rate was similar among treatment groups in Trials 1 (T-7 = 55.6%; T-10 = 18.8%; T-11.5 = 26.7%) and 2 (T-7 = 85.2%; T-11.5 = 93.6%). The three treatments efficiently synchronized estrus. T-7 and T-11.5 protocols resulted in high estrus synchrony and conception rates when adjusting the AI time according to interval of estrus.
Keywords: AI; Caprine; PGF2 alpha analog; Prostaglandin; Reproductive performance